ショウワ キチ ニオケル デンパ オーロラ ノ シュツゲン トクセイ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 城, 功; シロ, イサオ; 坂元, 敏朗; サカモト, トシロウ; SHIRO, Isao; SAKAMOTO, Toshirou (国立極地研究所, 1973)
P(論文) Radio aurora occurrences on 112 MHz observed for nearly one year from April 1970 till February 1971 at Syowa Station the Antarctic were analized. Results obtained are summarized as follows: 1) The diurnal variation in the frequency of the radio echo occurrence correlates well with the magnetic Q-index. 2) The frequency of their occurrence in the morning sequence correlates comparatively well with absorption of the cosmic radio noise recorded by the riometer, but no definite relation is found in the evening sequence. 3) Most echoes in the dark winter have discrete structures, while those in the sunlit summer are characterized by diffuse ones. 4) The reflected echoes are generally weaker in the winter than in the summer. 5) The echoes in the winter are confined within the range from 300 to 400 km, while the range of those in the summer extends from 300 to 1100 km. 6) Radio auroras move northward in the morning and southward in the evening, at a speed of 500～600 m/s. departmental bulletin paper